VALORIZATION OF DATE SEEDS WASTES AS REINFORCEMENT FOR STARCH-GRAFTED-POLYPROPYLENE COMPOSITES Journal of Fundamental and Applied Sciences is licensed under aCreative Commons Attribution-NonCommercial 4.0 International License. Libraries Resource Directory. We are listed under Research Associations category.VALORIZATION OF DATE SEEDS WASTES AS REINFORCEMENT FOR STARCH-GRAFTED-POLYPROPYLENE COMPOSITES - Hamma, A; Dairi, B; Bouhelal, S (university of eloued -جامعة الوادي, 2022)
Paper discusses the possibility of incorporation of date seed waste as fillers (DSF) into starch-g-PP matrices compared to kenaf fibers (KF with two lengths) based composites. Three starch-g-PP matrices (G906PF, G906PJ and G720PJ) were studied in parallel to a fully PP one. The investigated composites loaded to 20 wt.%, showed differences in performance related, principally, to loading type (DSF, KF) and matrix used. Results showed an improvement of tensile and impact stress at break as well as Shore D hardness of starch-g-PP composites reinforced with date seed fillers (DSF) or kenaf fibers (KF). Further, tensile, storage and loss moduli increased also with loading. Vicat softening point of either KF or DSF/starch-g-PP composites was greater with higher values for KF composites. However, thermal stability of starch-g-PP composites was better when DSF was used
article
Keywords: Date seed fillers, starch-g-polypropylene, bio-composites, mechanical properties, waste valorization